2018
DOI: 10.24843/ejmunud.2018.v07.i05.p14
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Pelayanan Terhadap Persepsi Nilai Nasabah Yang Dimediasi Oleh Persepsi Risiko Studi Pada Nasabah LPD Pererenan Kabupaten Badung

Abstract: The risks faced by customers when using the services of LPD, with attention to and maintain the quality of the company provided to customers will be added value to the LPD. The purpose of this study to determine the effect of service quality on the perception of customer value mediated by risk perception. This research was conducted at LPD Pererenan Kabupaten Badung. The sample used is 100 customers. The technique of this research is purposive sampling and analysis technique used is path analysis technique. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
1
0
1
Order By: Relevance
“…The results of research conducted by Ananda (2018) state that the better the quality of service provided, the more impact it will have on increasing the perceived value consumers feel. Similar things were also found in research (Warman et al, 2019) ; (Mandala, 2018) ; (Ariany & Lutfi, 2021).…”
Section: The Influence Of Service Quality On Perceived Valuesupporting
confidence: 89%
See 1 more Smart Citation
“…The results of research conducted by Ananda (2018) state that the better the quality of service provided, the more impact it will have on increasing the perceived value consumers feel. Similar things were also found in research (Warman et al, 2019) ; (Mandala, 2018) ; (Ariany & Lutfi, 2021).…”
Section: The Influence Of Service Quality On Perceived Valuesupporting
confidence: 89%
“…Research states that service quality positively and significantly affects perceived Value (Warman et al, 2019). The same research results were found in (Mandala, 2018) (Ariany & Lutfi, 2021) and (Yogaswara & Pramudana, 2022).…”
Section: Introductionsupporting
confidence: 80%
“…The population used in this study are tourists who visit Buleleng Regency, the number of which in the latest BPS data is 224,209. In this study, the sample determination method used is probability sampling, which is a sampling technique that provides equal opportunities or opportunities for each element or member of the population to be selected as a sample, Rahyuda in (Wijaya & Mandala, 2018). The sample used was 100 tourists who visited Buleleng Regency.…”
Section: Methodsmentioning
confidence: 99%
“…Salah satu poin penting guna mempertahankan nasabah adalah dengan melakukan pelayanan yang baik. Tentunya nasabah akan beralih ketempat lain apabila pelayanan yang diberikan tidak maksimal (Astuti dalam Wijaya dan Mandala, 2018). Karena beraneka ragamnya superioritas LPD tersebut, maka terciptalah kualitas pelayanan masyarakat terhadap LPD.…”
Section: Pendahuluanunclassified